2019
DOI: 10.35940/ijitee.a4985.119119
|View full text |Cite
|
Sign up to set email alerts
|

Digital Franchising and Entrepreneurship: Effects of Digital Technology on the Relations of Business Process Participants

Abstract:  Abstract: One of the most popular forms of business in many industries of the world economy is franchising. The advance of franchising has changed the operational environment for economic entities and created the need to adjust operational processes, generate new knowledge and implement them in operations.The purpose of this paper is to analyse the potential of digital franchising and involved drivers of growth exploited by innovative franchisers in the long run.The paper provides an analysis and specifies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…En este punto, se utilizó el tipo de metodología cualitativa a través de la recolección de documentos de investigación. Primero, se afirma que la digitalización de las franquicias establece las bases para fomentar nuevas oportunidades, competencias y valores, lo que genera ventajas competitivas [11]. En ese sentido, se deduce que través de un patrón consistente la transformación digital impulsa a las pymes a buscar una mayor eficacia en las actividades existentes para generar valor, esto seguido de la unión de fuentes de nuevo valor que son relacionadas con la eficiencia a partir de las actividades expuestas [18] También, es relevante la comunicación dentro de la red de franquicias a través de foros de discusión y constantes reuniones en temas de la gestión de datos de clientes con la finalidad de difundir las buenas prácticas que se han implementado a nivel local [29].…”
Section: Transformación Digital E Internacionalización De Franquiciasunclassified
“…En este punto, se utilizó el tipo de metodología cualitativa a través de la recolección de documentos de investigación. Primero, se afirma que la digitalización de las franquicias establece las bases para fomentar nuevas oportunidades, competencias y valores, lo que genera ventajas competitivas [11]. En ese sentido, se deduce que través de un patrón consistente la transformación digital impulsa a las pymes a buscar una mayor eficacia en las actividades existentes para generar valor, esto seguido de la unión de fuentes de nuevo valor que son relacionadas con la eficiencia a partir de las actividades expuestas [18] También, es relevante la comunicación dentro de la red de franquicias a través de foros de discusión y constantes reuniones en temas de la gestión de datos de clientes con la finalidad de difundir las buenas prácticas que se han implementado a nivel local [29].…”
Section: Transformación Digital E Internacionalización De Franquiciasunclassified
“…Franchises that invest in technologies such as mobile apps, online ordering platforms, and personalized marketing tools can effectively connect with tech-savvy customers, resulting in increased customer loyalty. These technologies cater to the modern consumer's high regard for convenience and personalization (Gladilina et al, 2019). One of the factors driving technology use in the franchise business is to facilitate customer interaction with the franchise.…”
Section: Factors Influencing the Use Of Technology In Franchise Businessmentioning
confidence: 99%
“…With the enhancement in digital technology, it represents a significant force for franchising development. Gladilina (2019) [8] has done the studied and shown that several local or global factors drive transformation from traditional to digital franchising. Digital transformation could be application in franchise system management to create competitive advantage.…”
Section: Franchising In Digital Eramentioning
confidence: 99%